Identification of different Borrelia burgdorferi genomic groups from Scottish ticks. Issue 2 (1st April 2000) - Ling, C L; Joss, A W L; Davidson, M M; Ho-Yen, D O
Abstract : Aim —To characterise 12 Borrelia burgdorferi sensu lato isolates cultured from ticks collected in the Highlands of Scotland. Methods —Three molecular methods were used: an outer surface membrane protein A (OSP A) gene polymerase chain reaction (PCR) designed to give different molecular weight products with different genomic groups, randomly amplified polymorphic DNA (RAPD) analysis, and ribosomal RNA (rRNA) gene PCRs using genomic group specific primers. Results —All of the molecular methods used were quick and easy to perform and capable of differentiating between the different genomic groups of B burgdorferi sensu lato. All 12 tick isolates were characterised successfully with each method: five were characterised as B afzelii and seven were characterised as B burgdorferi sensu stricto. RAPD also identified differences within these genomic groups. Conclusions —From this study, it is now known that at least two different B burgdorferi sensu lato genomic groups are present in the Highlands of Scotland: B afzelii and B burgdorferi sensu stricto. This information can now be used to develop appropriate serological tests, which should improve the diagnosis and management of patients with Lyme disease in Scotland. The molecular methods chosen were found to be useful typing tools and will allow rapid identification of any future isolates.